Source code and data for the PhD Thesis "Metrics of graph-based meaning representations with applications from parsing evaluation to explainable NLG evaluation and semantic search" - Opitz, Juri (Universität, 2024)
This dataset contains source code and data used in the PhD thesis "Metrics of Graph-Based Meaning Representations with Applications from Parsing Evaluation to Explainable NLG Evaluation and Semantic Search". The dataset is split into five repositories: S3BERT: Source code to run experiments for chapter 9 "Building efficient and effective similarity models from MR metrics". amr-metric-suite, weisfeiler-leman-amr-metrics: Source code to run metric experiments for chapters 4, 5, 6. amr-argument-sim: Source code to run experiments for chapter 8 "Exploring argumentation with MR metrics". bamboo-amr-benchmark: Benchmark for testing and developing metrics (chapter 5).